Lupoid cutaneous leishmaniasis: A report of three cases from nonendemic area - Lalit Kumar Gupta; Soniya Meena; Ashok Kumar Khare; Manisha Balai; Asit Mittal; Sharad Mehta (Wolters Kluwer Medknow Publications, 2017)
The typical clinical presentations of cutaneous leishmaniasis are nodules, ulcer, nodulo-ulcerative lesions and crusted plaques. Besides classical clinical picture, several unusual and atypical clinical presentations of the disease have also been reported. Herein, we report three cases of lupoid cutaneous leishmaniasis to highlight the extended clinical spectrum of CL. Tissue smears were positive for Leishman-Donovan (LD) bodies. All patients were treated by azole antifungals with favorable response.